Credit Screening System Selection - Long, Michael S. (Journal of Financial and Quantitative Analysis, 1976)
Recent financial literature has discussed how a creditor should determine its investigation and extension policy. Mehta [8, 9] has developed a sequential process for credit extension, and others [1, 2, 4, 7, 10, 12, 14] have used credit-scoring functions to develop decisions rules. Instead of discussing the use of a particular system or the development of a new system, this paper shifts the focus to selection of the best of alternative systems. Different creditors face different profit-loss ratios on loans, business volume, and prior probabilities of good and bad customers. Furthermore, since the alternative systems have different initial costs, effectiveness, and investigation costs per application, no one system is optimal for all creditors. Finally, any credit-scoring alternative declines in effectiveness over time. Measurement of the overall effectiveness of a system requires that the optimal time between updating the system be known.